ISLAMIC EDUCATION MANAGEMENT AND GRADUATE QUALITY IMPROVEMENT: EVALUATIVE INSIGHTS FROM THE LITERATURE - Selviani, Ana Mega; Nurjannah, Amalliya; Elice, Deti; Masayu, Sovia (Jurnal Manajemen Pendidikan, 2025)
Islamic education institutions are increasingly required to demonstrate graduate quality that reflects both strong religious values and competitive competencies in contemporary social and labor contexts. This study aims to critically evaluate the scholarly literature on Islamic education management and its contribution to graduate quality improvement. Adopting a narrative and evaluative literature review approach, this article synthesizes theoretical and empirical studies published between 2019 and 2025 in internationally indexed journals and reputable national journals. The analysis reveals that effective Islamic education management particularly value-based and transformational leadership, integrated curriculum management, and outcome-oriented quality assurance plays a significant role in enhancing graduate quality. However, the findings also indicate persistent challenges, including compliance driven evaluation practices, fragmented outcome assessment, and limited empirical linkage between management interventions and graduate centered indicators. The discussion highlights the need for more integrative evaluative frameworks that connect managerial effectiveness with holistic graduate outcomes encompassing intellectual competence, ethical formation, and employability. This study contributes by offering evaluative insights that clarify conceptual fragmentation in the literature and identify priority areas for future research.